2020
DOI: 10.3390/antibiotics9120922
|View full text |Cite
|
Sign up to set email alerts
|

Gram-Negative Bloodstream Infection: Implications of Antimicrobial Resistance on Clinical Outcomes and Therapy

Abstract: The age- and sex-adjusted incidence rate of Gram-negative bloodstream infection (GN-BSI) is 84 [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…Several studies compared short and prolonged antibiotic therapy for GNB BSI in hemodynamically stable patients in terms of mortality and B recurrence. The same survival rates were found in the two treatment groups [175][176][177][178].…”
Section: Treatment Duration: Short Courses or Long Courses? Combinati...supporting
confidence: 79%
See 2 more Smart Citations
“…Several studies compared short and prolonged antibiotic therapy for GNB BSI in hemodynamically stable patients in terms of mortality and B recurrence. The same survival rates were found in the two treatment groups [175][176][177][178].…”
Section: Treatment Duration: Short Courses or Long Courses? Combinati...supporting
confidence: 79%
“…Prolonged courses (>10–14 days) of intravenous antibiotics have been recommended for SAB because of concerns that infective endocarditis, deep infective foci, or metastatic infections might be present but not diagnosed [ 175 ]. A systematic review on the length of treatment of GNB secondary to UTI reported that the current limited evidence may corroborate that SCAb are as effective at obtaining clinical recovery microbiological eradication as longer courses [ 176 ]. Uno et al performed a study suggesting that acute cholangitis with Gram-negative bacillary bacteremia can be treated safely with a shorter antimicrobial treatment duration of <14 days [ 166 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mortality rate of this study was 10.86% which was lower than that in the USA (vs 12–15%). 4 However, this was only a result from one hospital and data were not available at the country level in China. However, the mortality rate of BSI was higher than that of other kind of infections, so preemptive treatment and optimization of treatment plan for BSI were very important to save patients’ lives.…”
Section: Discussionmentioning
confidence: 97%
“…2,3 GNBSI accounts for 279,000 cases and 33,500-41,900 deaths annually in the USA based on the current population. 4 Although the mortality rate did not rise, increasing antimicrobial resistance rates of GNBSI isolates, especially the emerging of multidrug resistant (MDR, non-susceptible to at least one agent in ≥3 classes of antibiotics) isolates, the extended spectrum beta-lactamases (ESBLs) producing isolates and carbapenem-resistant (CR) isolates have become one of the greatest threats to global health and a common drug-resistant pattern with a quite high epidemic trend around the world. [5][6][7][8] Therefore, fully understanding the epidemiological of GNBSI and drug resistance data was essential for selecting empirical antibacterial agents as well as optimizing antibiotic therapy regimen.…”
Section: Introductionmentioning
confidence: 99%